PERKEMBANGAN HUKUM ISLAM PADA MASA UMAR IBN KHATTAB (634-644 M) - Nofrianti, Mami (IAIN Batusangkar, 2018)
Islamic law is a law originating from and being part of the Islamic religion. Caliph Umar can be said to be the pioneer of legislation in an Islamic state. He has created a new paradigm in Islamic history. The development of Islam during the Caliph Umar to expand the Islamic region had a brilliant result. With the expansion of the Islamic region, the need for community education and fostering activities also increased. It was caused by people who had just converted to Islam in various conquered areas clearly needed guidance in the practice of Islamic application. Therefore, Islamic law had also undergone development from the previous period. The source of Islamic law in the era of Umar apart from the Qur'an and Sunnah was also carried out by Ijtihad. The method in this study was a library research, by collecting, reading, and studying books that have something to do with this discussion. At first glance Umar's decisions or Ijtihad seemed to contradict the provisions of the Qur'an, but if it was examined the nature of the verses in the framework of the overall purpose of Islamic law, the ijtihad carried out by Umar Ibn Khattab did not contradict with the meaning of the verses of the law.